Concise Synthesis of Goniothalesdiol A - Zeng, Ping Li; Zhou, Junhui; Yang, Xuechao; Wang, Dong; Dong, Zhibing (Letters in Organic Chemistry, 2022)
A concise and efficient synthesis of styryllactone derivative, goniothalesdiol A, has been achieved in the six longest linear steps with 17.7% overall yield. The key steps of our synthesis involved PdCl2-mediated Wacker-type oxidative cyclisation and one-pot tandem Wittig olefination- Michael addition.
Keywords: Wacker oxidation